Comparison and Correction of Thermo-Luminescent Responses in Different Neutron Fields - Samaneh Baradaran; Mehran Taheri; Amir Moslehi (Iranian Journal of Medical Physics, 2021)
Introduction: Neutron dosimetry is a challenging subject in radiation protection. Responses of neutron dosimeters mostly depend on the neutron energy spectrum. Dosimeter response corresponding to a dose-equivalent in the calibration field is different from responses in other neutron fields. Consequently, the dose estimated by neutron dosimeters may be associated with great uncertainty. Therefore, the present study aimed to modify the response in different neutron fields in order to reduce this uncertainty. Material and Methods: Thermo-luminescent dosimeters (TLDs) are widely used to determine neutron dose-equivalent. In the present study, a set of TLD-600 and TLD-700 dosimeters included in a TLD card was utilized to determine the response to “fast” neutrons of 241Am-Be,252Cf, and 239Pu-Be standard fields in four dose-equivalents of 5, 10, 15, and 20 mSv. Meanwhile, 241Am-Be was regarded as the calibration field.  Results: As evidenced by the obtained results, for equal dose-equivalents, the original responses in 252Cf and 239Pu-Be fields are smaller, compared to those in the 241Am-Be filed. The maximum discrepancies were obtained at 26.8% and 42.5% occurring at 20 and 5 mSv, respectively. After the application of a correction factor equal to the average of relative responses (i.e., in 241Am-Be to two other fields) corresponding to all dose-equivalents considered, these differences reduced to 12.4% and 21.7%. Conclusion: It can be concluded that the correction method used in the present study could enhance the accuracy of dose estimated by TLDs in fast neutron fields.